The Implementation of Feedback in the English Classes of Bengali Medium Schools (Global Journal of Human-Social Science, 2015)
This research investigated how feedback is implemented in the English language classes of the Bengali Medium Secondary Schools. In research studies, it has been shown that feedback is an essential component in all learning contexts and serves a variety of purposes including evaluation of students' achievements, development of students' competences and understanding, and elevation of students' motivation and confidence. By investigating from the perspectives of both the teachers and the students, this research attempted to find out the present conditions of teachers' feedback in the classroom setting that is trying to reduce the discrepancy between the current and desired amount of learning for the students to bridge their learning gap. This research conducted both qualitative and quantitative study that are reflected in the students' surveys and teachers' interviews which are analyzed with individual interpretation and comparison between the non -government and government Bengali medium schools on basis of the research questions.
Keywords: quantitative study; analyzed; individual interpretation; research questions